The Child's Civil Relationship under Indonesia's Compilation of Islamic Law: Reconciling Legal Legitimacy, Biological Paternity, and Guardianship Obligations - Astuti, Widia; Sri Wahyuni Ningsi; Hamzah (QISTHOSIA : Jurnal Syariah dan Hukum, 2025)
This study analyzes the determination of a child's civil status (including lineage, inheritance, guardianship, and marriage) under the Compilation of Islamic Law (KHI), by identifying inconsistencies within its provisions. The analysis applies legal interpretation to specific articles of the KHI. Article 53 paragraph (1) of the Compilation of Islamic Law states that a woman who is pregnant outside of marriage may be married to the man who caused the pregnancy. However, from a linguistic perspective, the use of the word may in Article 53 paragraph (1) opens the possibility for interpretation that another man, not responsible for the pregnancy, may also marry the pregnant woman. As a consequence, a man who is not the biological father of the child may still acquire a civil legal relationship with the child due to his legal marriage to the mother. Although not the biological father, the man’s legal status toward the child born from his wife is recognized in civil law. This interpretation aligns with the Constitutional Court Decision Number 46/PUU-VIII/2010, which reinterprets Article 43 paragraph (1) of the Marriage Law. Furthermore, Article 53 paragraph (1) of the Compilation of Islamic Law opens new opportunities for the recognition of civil status of children born from unregistered marriages or from the marriage of a pregnant woman to a man who is not the biological father.